1992
DOI: 10.1038/ng0492-56
|View full text |Cite
|
Sign up to set email alerts
|

Cretinism with combined hormone deficiency caused by a mutation in the PIT1 gene

Abstract: Cretinism is marked by irreversible mental and growth retardation. We describe here an entirely new case of cretinism showing combined pituitary hormone deficiencies of thyrotropin, growth hormone and prolactin that appears to be caused by homozygosity for a nonsense mutation in the gene for the pituitary specific transcription activator, Pit-1/GHF-1 (designated PIT1 in humans for pituitary specific factor 1). This is the first report in humans of a defect in a transcription activator causing deficiency of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
137
0
6

Year Published

1994
1994
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(145 citation statements)
references
References 41 publications
2
137
0
6
Order By: Relevance
“…It was initially identified and cloned based on its ability to bind and transactivate the expression of the mammalian prl and gh genes. These findings were underscored by the identification of spontaneous mutations in the human and murine pit1 gene, which cause an absence of lacto-, thyro-, and somatotrope differentiation, thereby defining the so-called Pit1 lineage (Li et al, 1990, Tatsumi et al, 1992, Pfaffle et al, 1992, Radovick et al, 1992. The more recently identified zebrafish pit1 mutants lack exactly the same three AH cell types, indicating that the function of Pit1 during AH lineage specification is highly conserved among the different vertebrate classes (Nica et al, 2004).…”
mentioning
confidence: 99%
“…It was initially identified and cloned based on its ability to bind and transactivate the expression of the mammalian prl and gh genes. These findings were underscored by the identification of spontaneous mutations in the human and murine pit1 gene, which cause an absence of lacto-, thyro-, and somatotrope differentiation, thereby defining the so-called Pit1 lineage (Li et al, 1990, Tatsumi et al, 1992, Pfaffle et al, 1992, Radovick et al, 1992. The more recently identified zebrafish pit1 mutants lack exactly the same three AH cell types, indicating that the function of Pit1 during AH lineage specification is highly conserved among the different vertebrate classes (Nica et al, 2004).…”
mentioning
confidence: 99%
“…Some of these mutations can be understood in terms of their negative effects on DNA binding. For instance, the nonsense mutations R172X and E250X (using a numbering scheme based on the whole protein, where X stands for a stop codon) cause deletions of protein segments important for DNA binding (Tatsumi et al 1992;Irie et al 1995). The missense mutation RI43Q substitutes a critical arginine residue with a glutamine (Ohta et al 1992).…”
Section: Cphdmentioning
confidence: 99%
“…Other studies have shown that GH deficiency is associated with serious functional deficits and increased risk of premature death due to cardiovascular complications (Sacca et al, 1994;Bates et al, 1996). Mutations similar to Pit-1 and Prop-1 have been reported in humans and those children affected require thyroid hormone and GH treatment (Tatsumi et al, 1992;Pfaffle et al, 1996;Fluck et al, 1998).…”
Section: Growth Hormone/insulin-like Growth Factor 1/insulinmentioning
confidence: 99%